Spectral amplitude coding OCDMA using and subtraction technique - Syed Alwee Aljunid, Syed Junid; Hasoon, Feras N.; Samad, M.D.A.; Mohamad Khazani, Abdullah; Othman, M.; Sahbudin, Shaari (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org